ANALYSIS OF FINANCIAL DISTRESS DETERMINANTS IN SECURITIES COMPANIES AS MEMBERS OF THE EXCHANGE IN INDONESIA - Catur Karyanto Pilih; Wisnu Mawardi (RADJA PUBLIKA, 2025)
Financial distress in securities companies can be an early indicator of potential financial failure that has a systemic impact on capital market stability. In the context of global and domestic economic dynamics, including the COVID-19 pandemic, securities companies face complex pressures from both internal and external sides. Therefore, early identification of factors that influence financial distress is very important in maintaining business continuity and protecting investors. This study aims to examine the effect of profitability, liquidity, solvency, capital structure, company size, corporate governance, and macroeconomic factors on the probability of financial distress in securities companies that are members of the stock exchange in Indonesia. This study is motivated by the importance of early detection of the financial condition of securities companies that have the potential to experience financial distress, especially in the context of market dynamics and external challenges such as the COVID-19 pandemic. The research method used is logistic regression analysis of secondary data from securities companies, namely93 securities companies are members of the stock exchange in Indonesia during the period 2018 to 2023.The variables analyzed include financial ratios (ROA, ROE, NIATTA, CR, TAANC, DER, TLOE, ECCABC, WACC, TA), corporate governance indicators (GCG), and macroeconomic indicators (GDP, INF, IHSG, BI7DRR). The results of the study indicate that profitability and liquidity do not have a significant effect on the probability of financial distress. On the contrary, the variables of solvency, capital structure, and company size are proven to have a significant effect in reducing the possibility of financial distress. In particular, the variables of Debt to Equity Ratio (DER) and ECCABC have the strongest influence in predicting this risk. The corporate governance variable does not show a significant effect, which indicates that the governance dimension is not always in line with the indicators of financial distress. Meanwhile, macroeconomic variables such as GDP, inflation, and the composite stock price index (IHSG) are proven to be significant in reducing the probability of financial distress, while the BI benchmark interest rate (BI7DRR) does not have a significant effect.